Comparison of Premiums of Chinese and European Companies in Mergers and Acquisitions in Europe - Urbšienė, Laimutė; Nemunaitytė, Viktorija; Zatulinas, Artūras (Organizations and Markets in Emerging Economies, 2015)
The goal of the study is to analyse whether Chinese Mainland companies were paying higher premiums for similar target companies in Europe in comparison with Europe-based companies during the period of 2000-2013. To determine the difference between premiums paid by Chinese and European companies, two samples were analysed: one represented all Chinese acquisitions in Europe which matched the set criteria, another included comparable European targets acquired by European companies. Quantitative research methods were applied to measure statistical difference in the premiums of the two samples. Results of the research indicate that the average premiums paid by Chinese companies are double the size of the European acquisition premiums for the similar target company in Europe. Significant evidence suggests that premiums of Chinese and European companies for similar targets in Europe are not equal.